Contribuições do TCC para a formação de professores pedagogos : um estudo de caso em uma instituição de ensino superior - Moura, Josiel da Rosa (2017)
This research was located in the field of teacher training, understanding that research is part of this process, especially with regard to the Course Completion Work (CBT). He sought the understanding of research practices developed in the course of Pedagogy and his contributions to the formation of pedagogues-teachers. It takes as corpus of investigation the words of the academics of the Pedagogy course of a Public Institution of Higher Education regarding the learning and the experiences obtained in the CBT. It is a qualitative approach to research using the principles of case study. Semi-structured interviews were used as instruments of data collection. The interviews were recorded with audio equipment, later transcribed. Informants after agreeing to their use, according to the Free and Informed Consent Term were not identified, preserving their identity. In order to deal with the information obtained, the methodology of Discursive Textual Analysis (ATD) was used, from which categories were constructed. Through the help of the ATD methodology the metatext was developed, which maintained a fruitful dialogue with some theorists who deal with the subject, from which the following categories emerged: Construction of CBT: articulation theory and practice, Research in teacherteacher training ; Senses attributed from the CBT research experience. The results of the research point to divergent conceptions both regarding the contributions in the research for the formation of the future teachers, as well as for the subject of the curriculum of the course, which brings the teaching of the research, and not of the research as the guiding thread of learning in Its educational principle.